A New Destination on the Palm? The Moderating Effect of Travel Anxiety on Digital Tourism Behavior in Extended UTAUT2 and TTF Models - Sun, Jiaojiao; Guo, Yingzhi (Frontiers in Psychology, 2022)
Digital tourism has developed rapidly, especially in museums. However, as people become increasingly familiar with digital museums, their use intentions and behavior have changed. Taking the Digital Palace Museum in China as an example, applying the PLS-SEM method, this study uncovers visitors’ use intentions and actual use behavior for digital museums by integrating the new UTAUT model (UTAUT2) and TTF model (TTF under social distancing), and introduces the PATS(Pandemic Anxiety Travel Scale) model to reveal how pandemic anxiety promotes the transformation of use intentions into use behavior more easily. The results show that performance expectations, hedonic motivations, habits, and task-technology-fit positively affect use intentions for digital museums. However, the price-saving orientation negatively affects use intentions. Pandemic anxiety moderates the effect of use intentions on actual behavior. When travel anxiety is relatively high, use intentions have a greater effect on use behavior for digital museums. The results reveal the influencing factors on use intentions of digital museums and the moderating effect of pandemic anxiety on the relation between use intentions and actual behavior.